The effect of dietary nitrate and canola oil alone or in combination on fermentation, digesta kinetics and methane emissions from cattle - Villar, Maria Laura; Hegarty, Roger Stephen; Nolan, John V.; Godwin, Ian R.; McPhee, Malcolm J. (Elsevier, 2020)
Nitrate and lipids have been recognized as effective dietary additives to reduce enteric methane (CH4) production. The objective of this experiment was to evaluate the effects of nitrate (NO3¯) and canola oil, alone or in combination, on enteric CH4, volatile fatty acid (VFA) concentrations, digesta kinetics and outflow of DM and microbial non-ammonia nitrogen (MicNAN) from the rumen of cattle. Four rumen-cannulated steers were used in the experiment which was designed as 4×4 Latin Square with four 21-d periods and four treatments. Dietary treatments consisted of a control diet (CON: 400 g/kg lucerne chaff and 600 g/kg barley grain), NO3¯ (CON+20 g NO3¯/kg), O (CON+50 g canola oil/kg), and NO3¯+O (CON+20 g NO3¯/kg + 50 g canola oil/kg)with all inclusions expressed as g/kg as-fed. Exogenous markers (Co-EDTA, Yb-acetate and 15NH4Cl) were continuously infused into the rumen over 4 d to estimate digesta flow and rumen N outflow while whole tract digestibility (DMD) was determined using chromic oxide. Compared with the CON diet, feeding the NO3 ¯+O diet reduced (P < 0.01) methane yield (MY, g CH4/kg DMI) by 25%, daily methane production (DMP, g CH4/d) by 26% (P < 0.01) and the rumen mean retention time (MRT; P < 0.05). Nitrate containing diets reduced DMD (P < 0.01). Total VFA did not differ between treatments (P > 0.05) but NO3¯-containing diets increased acetateproportion (P < 0.01) whereas feeding the O diet increased propionate proportion (P < 0.01). Oil-containing diets reduced rumen volume (P < 0.01). The rumen protozoa concentration was reduced by including NO3¯ and canola oil alone or in combination in the diet of cattle (P < 0.05). This experiment demonstrates that feeding NO3¯+O has a synergistic effect on reducing methanogenesis from beef cattle which is consistent with NO3¯ and canola oil having complementary mechanisms for suppressing enteric CH4 production. Reducing methanogenesis by feeding NO3¯+O in this experiment did not improve the flow of MicNAN from the rumen (g MicNAN/d), microbial growth efficiency (g MicNAN/digestible organic matter intake, DOMI) or the proportion of microbial N derived from rumen NH3.